miR-141 modulates osteoblastic cell proliferation by regulating the target gene of lncRNA H19 and lncRNA H19-derived miR-675 - He, Peiheng (Am J Transl Res, 2016)
Increasing evidence has reported the significant roles of lncRNA or miRNAs in the biology of various diseases. This study was aimed to elucidate the potential roles of miR-141 and lncRNA H19 and H19-derived miR-675 in regulating osteoblasts proliferation and apoptosis and to explore its potential mechanism. miR-141 mimic or miR-141 inhibitor or siRNA-H19 or miR-675 inhibitor was transfected into human hFOB1.19 cells. The effects or miR-141 expression on H19 or miR-675 expression, on osteoblasts proliferation and apoptosis were analyzed. Moreover, effects of H19 and miR-675 expression on cell proliferation were also analyzed. The results showed that miR-141 was down-regulated in both hFOB1.19 cells and osteosarcoma tissues. The overexpressed miR-141 suppressed H19 and miR-675 expression in hFOB1.19 cells. Besides, miR-141 suppression significantly increased cell viability but this effect was blocked by silencing H19 or miR-675 inhibitor, which is similar to the effects on VEGF and IGF2 expression. Furthermore, miR-141 overexpression induced osteoblasts apoptosis, but decreased the levels of caspase-3 and the Bcl-2/Bax ratio. Taken together, our study revealed that tumor-suppressor miR-141 overexpression suppressed osteoblasts proliferation but induced apoptosis through down-regulating H19 or miR-675 in osteosarcoma. This study may provide theoretical basis for illustrating the interaction between lncRNA and miRNAs in osteosarcoma and for the therapeutic target of miR-141 in osteosarcoma treatment.